Non linear analysis of vibrations generated by a contact with friction - Meziane, Anissa; Baillet, Laurent (European Journal of Computational Mechanics, 2010)
The aim of this paper is to study vibrations generated at contact with friction for two different applications. The first one is an investigation of friction-induced vibrations of a beam-on-beam system in contact with friction. For this study the complementary use of linear and nonlinear analyses drives to the understanding of physical phenomenon induced in these vibrations. The second parts consists in investigating numerically dynamic rupture of a bimaterial interface. The numerical Finite Element model is composed of two homogeneous and isotropic elastic solids which are brought in contact with friction by remote normal compression and shear traction. The rupture is nucleated by decreasing instantaneously the friction coefficient to zero at nucleation area. The properties of the obtained ruptures (velocity, generated waves, interface state…) are analyzed.